2017
DOI: 10.5755/j01.ee.28.3.13651
|View full text |Cite
|
Sign up to set email alerts
|

Project Management Methods in Projects Co-financed by EU Funds

Abstract: This paper deals with the management of projects co-financed by European Union funds (structural funds and the Cohesion Fund) in the Czech Republic (EU projects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Future efforts should focus on increasing awareness of international standards and fostering collaboration among stakeholders. Older research at the national level confirms that this is not the case and that there is not enough support from support providers (Kostalova et al, 2015;Kostalova et al, 2017). Recent research focused on the knowledge and use of project management tools in practice, carried out among project managers of projects financed by EU Funds (Kostalova, et al, 2023) confirmed that awareness of individual international standards of project management at the national level is relatively low (the most well-known was the PRINCE2 standard), the use of these standards in practice was even lower.…”
Section: Discussionmentioning
confidence: 99%
“…Future efforts should focus on increasing awareness of international standards and fostering collaboration among stakeholders. Older research at the national level confirms that this is not the case and that there is not enough support from support providers (Kostalova et al, 2015;Kostalova et al, 2017). Recent research focused on the knowledge and use of project management tools in practice, carried out among project managers of projects financed by EU Funds (Kostalova, et al, 2023) confirmed that awareness of individual international standards of project management at the national level is relatively low (the most well-known was the PRINCE2 standard), the use of these standards in practice was even lower.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature on management sciences, there are positions on the issues concerning management and measuring the efficiency of various types of projects. Among them are, for example, considerations regarding project management methods for projects co-financed by EU funds (Kostalova et al, 2017), proposals for methods for evaluating the efficiency of public, investment, IT and other projects. In these publications, little attention is devoted to the issue of project social efficiency measurement.…”
Section: Efficiency Evaluation In Project Managementmentioning
confidence: 99%
“…Especially in previous PPs, the issue of project management was not prioritized by subsidy providers, although it was generally recommended, but the actual use in practice was insufficient (Gazda et al, 2011;Kostalova et al, 2017;Zurga, 2018). There are some improvement activities like courses of project management focused on ESIF financed projects, studying programs or subjects at universities (Stanickova, 2016), but it is a question, if it is sufficient.…”
Section: Introductionmentioning
confidence: 99%